Faute de langue, faute de traduction - Pleciński, Jacek (Verbum – Analecta Neolatina, 2006)
This paper highlights the difference between linguistic error and translation error. In doing so so, the author provides an analysis of two "extreme" translations. The first one, by a Polish female student of French, cumulates all imaginable mistakes (concerning both comprehension and translation into the foreign language). The second one is a one-sentence subtitle from a film, inadvertently translated from Spanish into (native) Polish. The translation (which should have been carried out with a word-for-word translation) was put into Polish by the translator using a dynamic equivalent of an idiomatic expression. The dynamic equivalent does not match the scene in the film.